PPL: Structured Parallel Programming Meets Rust - Besozzi, Valerio (Proceedings - Euromicro Workshop on Parallel and Distributed Processing, 2024)
In this paper, we present Parallelo Parallel Library (PPL), a novel Rust library for structured parallel program-ming. Rust's fearless concurrency concept makes it a promising language for parallel application development. We present the development progress of Parallelo Parallel Library (PPL) and report preliminary performance results, comparing it to existing popular Rust libraries. Our results show that PPL provides robust support for parallel programming through high-level abstractions, delivering performance that matches or exceeds current state-of-the-art in the Rust ecosystem.